2023
DOI: 10.3390/nano13121885
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Temperature-Dependent Mechanical Properties for SWCNT/Cu Nanocomposite Metamaterials: A Molecular Dynamics Study

Abstract: Single-walled carbon nanotube (SWCNT) is a promising candidate for strengthening nanocomposite. As the matrix of nanocomposite, a single crystal of copper is designed to be in-plane auxetic along the crystal orientation [1 1 0]. In that way, the nanocomposite could also be auxetic when enhanced by (7, 2) a single-walled carbon nanotube with relatively small in-plane Poisson’s ratio. A series of molecular dynamics (MD) models of the nanocomposite metamaterial are then established to study mechanical behaviors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Carbon nanotubes (CNTs), as one of the ideal potential fillers for nanocomposites [11], exhibit superior excellent mechanical properties compared to carbon fiber. In the paper "Chirality-Dependent and Intrinsic Auxeticity for Single-Walled Carbon Nanotubes", Zhang et al [12] discovered the auxetic nature of CNTs.…”
Section: Nano Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs), as one of the ideal potential fillers for nanocomposites [11], exhibit superior excellent mechanical properties compared to carbon fiber. In the paper "Chirality-Dependent and Intrinsic Auxeticity for Single-Walled Carbon Nanotubes", Zhang et al [12] discovered the auxetic nature of CNTs.…”
Section: Nano Reinforcementmentioning
confidence: 99%
“…Their study showed that the auxeticity of CNTs was mainly determined by the stretch of C-C bonds, and the critical strain was achieved when the negative contribution of bond stretch to Poisson's ratio counteracted the positive contribution of angle variation. In their subsequent work, they proposed the atomic structures of auxetic nanocomposites [11] and verified their negative Poisson's ratios using MD methods. Moreover, the mechanical performance of auxetic nanocomposites greatly surpassed that of existing man-made reentrant auxetic materials [13,14].…”
Section: Nano Reinforcementmentioning
confidence: 99%